2021
DOI: 10.3892/ijo.2021.5204
|View full text |Cite
|
Sign up to set email alerts
|

The pterocarpanquinone LQB‑118 compound induces apoptosis of cytarabine‑resistant acute myeloid leukemia cells

Abstract: Acute myeloid leukemia (AML) is a complex hematological disorder characterized by blockage of differentiation and high proliferation rates of myeloid progenitors. Anthracycline and cytarabine-based therapy has remained the standard treatment for AML over the last four decades. Although this treatment strategy has increased survival rates, patients often develop resistance to these drugs. Despite efforts to understand the mechanisms underlying cytarabine resistance, there have been few advances in the field. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 68 publications
(111 reference statements)
1
5
0
Order By: Relevance
“…Hence, we studied the effect of treatments on cell viability, apoptosis, cell cycle progression and proliferation. First of all, we showed that cytarabine reduced cell viability and also increases apoptosis levels in THP-1 cells, as already demonstrated in other leukemia cell lines [38]. DFX and ELT instead did not affect cell viability when alone but exacerbated the effect of cytarabine, especially ELT, thus letting hypothesize…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Hence, we studied the effect of treatments on cell viability, apoptosis, cell cycle progression and proliferation. First of all, we showed that cytarabine reduced cell viability and also increases apoptosis levels in THP-1 cells, as already demonstrated in other leukemia cell lines [38]. DFX and ELT instead did not affect cell viability when alone but exacerbated the effect of cytarabine, especially ELT, thus letting hypothesize…”
Section: Discussionsupporting
confidence: 80%
“…ELT is able also to increase the pro-apoptotic effects of cytarabine, as demonstrated by cytofluorimetry and by the significant increase in BAX/Bcl-2 protein expression levels ratio. Bcl-2 protein is normally responsible for inhibiting apoptosis and in case of resistance to cytarabine it is often up-regulated [ 38 ]. An increase in BAX/Bcl-2 ratio indicates a prevalence of the pro-apoptotic processes and interestingly in THP-1 cell line this beneficial anticancer effect is evident only when cytarabine is combined with ELT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PR-619, a deubiquitinating enzyme (DUB) inhibitor, enhanced the antitumor effects of cisplatin in cisplatin-naïve and -resistant metastatic urothelial carcinoma both in vitro and in vivo through suppressing anti-apoptotic BCL-2 protein (132). The pterocarpanquinone LQB-118 compound induced apoptosis and reversed cytarabine-resistance in AML cells (133). Calmodulin can directly biund to DR5 in a Ca 2+ dependent manner.…”
Section: Othersmentioning
confidence: 99%